IMPLEMENTASI PEMBELAJARAN KONTEKSTUAL DALAM MENINGKATKAN KETERAMPILAN BERHITUNG ANAK USIA DINI - Annisak Annisak (Program Studi Pendidikan Islam Anak Usia Dini, 2024)
Early Childhood Education is an important foundation in shaping their cognitive, social and emotional development. In this domain, developing numeracy skills is one of the main focuses, because it has a significant impact. One approach that has attracted attention in improving numeracy learning in early childhood is the contextual learning approach. The research used is a qualitative descriptive approach using the Miles and Huberman approach, namely data reduction, data presentation and drawing conclusions. This research was carried out at KB Al-Farah Seri Kembang III. The children studied were aged 3-4 years. Based on the results of researchers' observations on children aged 3-4 years, children's cognitive development through contextual-based learning. The results of the analysis show that the percentage value for observing teacher and student activities in cycle I was 45.90% and increased in cycle II to 85.26%. These results show the suitability of the data received. Thus, it can be stated that contextual learning through the implementation of block media in the al-farah series kembang III can improve the numeracy skills of young children aged 3-4 years.